Implementing land trust in Bangladesh as a strategy for financing infrastructure and sustainable land management - Monzur Hossain; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2019)
As Bangladesh is a densely populated and land-scarce country, a land trust method can be applied in order to ensure productive and sustainable land management. We argue that land trust can be applied to managing agricultural land, khas land, real estate, and a delta in a sustainable manner in Bangladesh. The benefits of land trust include containing the spiraling of land prices, effective use of land, and ensuring a higher return from land. The main challenges for implementing land trust in Bangladesh include the lack of a legal and regulatory framework, lack of definition and scope of land trust, and weaknesses in land governance. We also argue that Bangladesh could even broaden the scope of traditional land trust to overcome financing bottlenecks of infrastructure investments. In these contexts, this paper discusses various methods of land trusts, challenges and opportunities of its implementation with some empirical evidences.
Keywords: Q15; R14; 330; land trust; land trust plus; spillover tax revenue; delta management; Bangladesh